ЖАНУБИЙ ОРОЛБЎЙИ ЧИЯБЎРИ CANIS AUREUS ЛАРИНИНГ DIOCTOPHYME RENALE НЕМАТОДАСИ БИЛАН ЗАРАРЛАНИШИ - Бердибаев, А.С.; Абдураҳмонов, А.Ш. (FAN va JAMIYAT, 2024)
This article describes the results of helminthological investigations conducted in chiabori in different natural geographical regions of Karakalpakstan. The damage indicators of the parasitic nematode D. renale in chiabori in 4 natural geographical regions of Karakalpakstan are presented. Also, information is given on the places of parasitism of D. renale nematode, intermediate and reservoir hosts in the development cycle.